Renewable Biomass-derived Carbon Dots: Innovations in Turn off-on Sensing of analytes - Yashika (My University, 2024)
In this work, we report a low-cost, environment-friendly technique for the synthesis of nitrogen-doped fluorescent carbon dots derived from biomass using the microwave pyrolysis technique, which was subsequently labeled as N-CDs. Clove powder was employed as a source of carbon, and glycine was used for nitrogen doping. As per the HR-TEM results, the average diameter of spherical-shaped N-CDs was 7.20 nm, with a range of 4-9 nm. Various characterization techniques like XPS and FTIR validated the presence of nitrogen and various other functional groups on the surface of N-CDs. The synthesized N-CDs exhibited excitation wavelength dependency properties and had a high quantum yield (QY) of 29.42%. These NCDs demonstrated exceptional photostability, favorable water solubility, and high optical stability. The fluorescent probe was found to be highly selective and sensitive for the detection of Fe (III) and Cr (VI) (with LOD values of 73.93 nM and 49.16 nM, respectively) through a fluorescence quenching (“Turn-Off”) mechanism. The electron-hole pair non-radiative recombination between functional groups on the surface of N-CDs and Fe (III)/Cr (VI) led to significant quenching. Furthermore, the functioning of carbon dots as a “Turn-On” sensor for fluoride ions (F-) differentiated the two complexes (N-CDs@Fe3+ & N-CDs@Cr6+). Fluoride ions, having a strong affinity towards Fe3+ ions, form a stable complex, sequestering its concentration and resulting in fluorescence recovery. This fluorescent nanoprobe showed an appreciable detection limit up to the micromolar range (1.69 µM) for F- ions. Hence, this probe is capable of rapidly and effortlessly identifying analytes (Fe (III) and Cr (VI)) and effectively distinguishing between the two in a mixture by utilizing F- ions.
Keywords: Photophysics; Renewable Biomass-derived Carbon Dots; Sensing; Dual Analytes; Fluorescence